Asuhan keperawatan anak dengan masalah resiko tersedak melalui edukasi kesehatan tentang tatalaksana kegawatdaruratan masalah tersedak - Mutiara Natalia; Rilyani Rilyani (THE JOURNAL OF Mother and Child Health Concerns, 2025)
Background: Toddlers are not yet able to distinguish between edible and inedible objects because they are in the oral phase and tend to put objects in their mouths, putting them at risk of choking. WHO (2011) recorded 17,537 cases of choking in children aged ≤3 years, with 59.5% caused by food, 31.4% by foreign objects, and 9.1% by other causes. Purpose: To report on pediatric nursing care, including providing education on emergency management of choking in children at home in Sukajaya District. Method: This was a quantitative descriptive study using a case study approach for nursing care (assessment to evaluation). Education was provided to improve mothers' knowledge in managing choking in children. Results: The evaluation of the choking management education conducted over two sessions showed a significant increase in knowledge among both respondents. Conclusion: Based on the results obtained after two sessions of education, both respondents showed a significant increase in knowledge regarding choking management in children